1977
DOI: 10.1152/jappl.1977.43.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Plasma norepinephrine responses of man in cold water

Abstract: The hypothermic stress of immersion in cold water stimulates release of norepinephrine from the sympathetic nervous system. The speed and pattern of this response was studied in six healthy men by serial measurements of plasma norepinephrine concentrations before, during, and after 60 min of immersion in 10 degrees C water. After immersion for 2 min, the mean norepinephrine concentration was increased from 359+/-32 (basal) to 642+/-138 pg/ml and rose gradually to a maximum of 1.171+/-226 pg/ml after 45 min of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(57 citation statements)
references
References 0 publications
1
56
0
Order By: Relevance
“…In general, noradrenaline concentration increases in the cold e n v i ro n m e n t , w i t h a d e c re a s e i n c or e ( r e c t a l ) temperature Therminarias et al, 1989). Johnson et al (1977) reported that the plasma noradrenaline response to cold water changes with skin temperature rather than rectal temperature. In the present study, T --sk during swimming in 23°C water was significantly lower than that in 28°C water, but the Tre was not.…”
Section: Discussionmentioning
confidence: 99%
“…In general, noradrenaline concentration increases in the cold e n v i ro n m e n t , w i t h a d e c re a s e i n c or e ( r e c t a l ) temperature Therminarias et al, 1989). Johnson et al (1977) reported that the plasma noradrenaline response to cold water changes with skin temperature rather than rectal temperature. In the present study, T --sk during swimming in 23°C water was significantly lower than that in 28°C water, but the Tre was not.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cytokines released from activated peripheral monocytes or activated peripheral monocytes themselves could circulate to the spleen and enhance the expression of proinflammatory cytokines in this tissue. Similarly, indirect activation of splenic immune cells via circulating catecholamines may be involved because cold stress increases plasma levels of catecholamines (18,26,46,52), which, in turn, can activate ␣2-adrenergic receptors and enhance proinflammatory cytokine levels (51). Because of this possibility, the present findings suggest that the upregulation of splenic cytokine gene expression to hypothermia under the conditions of the current experiments is not dependent on the sympathetic innervation to the spleen; however, an effect of the sympathetic nervous system via circulating catecholamines cannot be discounted.…”
Section: Discussionmentioning
confidence: 99%
“…Acute cold stress increases plasma concentrations of norepinephrine and epinephrine (18,26,46,52), changes the pattern of synchronized SND bursts (28), influences the frequency-domain relationships between discharge bursts in regionally selective sympathetic nerves (28), and produces nonuniform changes in the level of sympathetic nerve activity to selected target organs (28). With regard to the latter, hypothermia increases lumbar and decreases renal SND without significantly changing the level of activity in the splanchnic and adrenal nerves in anesthetized rats (28) and activates preganglionic cervical SND in anesthetized rabbits (27).…”
mentioning
confidence: 99%
“…For example, cytokines released from activated peripheral monocytes or activated peripheral monocytes themselves could circulate to the spleen and enhance the expression of proinflammatory cytokines in this tissue. Similarly, indirect activation of splenic immune cells via circulating catecholamines may be involved because cold-stress increases plasma levels of catecholamines (18,26,46,52), which in turn can activate α2-adrenergic receptors and enhance proinflammatory cytokine levels (51). Because of this possibility, the present findings suggest that the upregulation of splenic cytokine gene expression to hypothermia under the conditions of the current experiments is not dependent on the sympathetic innervation to the spleen; however, an effect of the sympathetic nervous system via circulating catecholamines cannot be discounted.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothermia, a common side effect of extreme cold environments, anesthesia, and serious traumatic injuries, alters the sympathetic nervous system and immune system regulation (8, 13-15, 21, 27-29, 47-50). Acute cold stress increases plasma concentrations of norepinephrine and epinephrine (18,26,46,52), changes the pattern of synchronized SND bursts (28), influences the frequency-domain relationships between discharge bursts in regionally selective sympathetic nerves (28), and produces nonuniform changes in the level of sympathetic nerve activity to selected target organs (28). With regards to the latter, hypothermia increases lumbar and decreases renal SND without significantly changing the level of activity in the splanchnic and adrenal nerves in anesthetized rats (28) and activates preganglionic cervical SND in anesthetized rabbits (27).…”
Section: Introductionmentioning
confidence: 99%